Analysis Of The Effect Of Equity And Liabilities On Profitability At PT Takaful Keluarga - ulya, an'nihayatul (Jurnal Ilmiah Ekonomi Islam, 2024)
The purpose of this study was to determine whether there is an influence between Equity and Liabilities on Profitability at PT. Family Takaful Year 2016-2021. The population used in this study is Equity, Liabilities and Profitability in PT. Takaful Family period 2016-2021. The data used in this study is secondary data taken from the official website of PT. Takaful Family year (2016-2021). This type of research is associative research. The sample collection technique used in this study is non-probability sampling, namely purposive sampling with samples used for 6 years. The analysis technique used in this study is regression analysis. The results of the regression analysis test show that equity has a significant positive effect on profitability, and liabilities have a significant positive effect on profitability.